Educational Financing Management at Islamic Education Institutions - Darifah, Udung Hari; Erihadiana, Mohamad (Bestari, 2023)
Financing has a crucial role in achieving educational goals that are productive, successful, innovative, efficient, and relevant. The realization of these components is contingent upon the availability of funding in Islamic educational institutions. In the realm of Islamic educational institutions, the factors that facilitate the achievement of an educational objective are the expenses or financial resources. The objective of this study is to provide a comprehensive description and analysis of topics pertaining to: budgetary strategies for allocating income, the utilization of funds in the field of education, and the oversight of financial management in education. The methodology employed in this study is descriptive, utilizing a qualitative approach. The data collection methods employed include interviews, observations, and documentation. Research subjects include principals, deputy principals, school treasurers, and school committees. The findings indicated that the principal spearheaded the budgeting procedure, which entailed the participation of the deputy principal, the head of the department, the treasurer, senior teachers, and the school committee. The analysis of education funding focuses on the financial aspect, emphasizing the need for both the school principal and internal stakeholders to have a comprehensive understanding of all expenses related to educational activities in order to effectively develop the RAPBS. The principle and deputy principal were responsible for overseeing the education financing of SMK Al Huda in Turalak, Ciamis district. The surveillance method is implemented by the meticulous observation of every incoming and outgoing financial transaction. Surveillance or scrutiny through the use of indirect observations, such as requiring the principal or treasurer's approval for any financial transactions. Financial scrutiny is conducted by analyzing the financial statements of each undertaken activity, which are submitted by the deputy principal or treasurer.